The name of Asclepius - Castro, Gilberto (2018)
This article analyzes the etymology of the name of the God Asclepius and its relation within the attributes of the God. So we hope to give a plausible and the most-possible-correct etymology with Indo-European origin, and we do compare the different etymological explanations given before that have caused some controversies because of its origin. Crucial importance has the fact that we emphasize the solar character of the God.